Rationale and design of the CardioMEMS Post‐Market Multinational Clinical Study: COAST - Martin R. Cowie; Pascal deGroote; Scott McKenzie; Marie‐Elena Brett; Philip B. Adamson; the CardioMEMS Post‐Market Study Investigators (ESC Heart Failure)
Abstract Aims Chronic heart failure reduces quality and quantity of life and is expensive for healthcare systems. Medical treatment relies on guideline‐directed therapy, but clinical follow‐up and remote management is highly variable and poorly effective. New remote management strategies are needed to maintain clinical stability and avoid hospitalizations for acute decompensation. Methods and results The CardioMEMS Post‐Market Study is a prospective, international, single‐arm, multicentre, open‐label study (NCT02954341) designed to examine the feasibility of haemodynamic guided heart failure management using a small pressure sensor permanently implanted in the pulmonary artery (PA). Daily uploaded PA pressures will be reviewed weekly to remotely guide medical management of patients with persistent NYHA Class III symptoms at baseline and a hospitalization in the prior 12 months. The study will enrol up to 800 patients from 85 sites across the United Kingdom, Europe, and Australia. The primary safety endpoint will assess device or system‐related complications or sensor failures after 2 years of follow‐up. Efficacy will be estimated after 1 year of follow‐up comparing HF hospitalization rates before and after sensor implantation. Observational endpoints will include mortality, patient, and investigator monitoring compliance, PA pressure changes, quality of life, and several pre‐defined subgroup analyses. Conclusions The CardioMEMS Post‐Market Study will investigate the generalizability of remote haemodynamic guided HF management in a number of national settings. The results may support the more widespread implementation of this novel clinical management approach.